Efficacy, Safety, and Acceptability of Misoprostol in the Treatment of Incomplete Miscarriage: A Systematic Review and Meta-analysis - Silva, Thiago Menezes da; Araujo, Moema Alves Guerra de; Simões, Ana Carolina Zimmermann; Oliveira, Ronnier de; Medeiros, Kleyton Santos de; Sarmento, Ayane Cristine; Medeiros, Robinson Dias de; Costa, Ana Paula Ferreira; Gonçalves, Ana Katherine (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To assess the efficacy, safety, and acceptability of misoprostol in the treatment of incomplete miscarriage.Data sources The PubMed, Scopus, Embase, Web of Science, Cochrane Library, and Clinical Trials databases (clinicaltrials.gov) were searched for the relevant articles, and search strategies were developed using a combination of thematic Medical Subject Headings terms and text words. The last search was conducted on July 4, 2022. No language restrictions were applied.Selection of studies Randomized clinical trials with patients of gestational age up to 6/7 weeks with a diagnosis of incomplete abortion and who were managed with at least 1 of the 3 types of treatment studied were included. A total of 8,087 studies were screened.Data collection Data were synthesized using the statistical package Review Manager V.5.1 (The Cochrane Collaboration, Oxford, United Kingdom). For dichotomous outcomes, the odds ratio (OR) and 95% confidence interval (CI) were derived for each study. Heterogeneity between the trial results was evaluated using the standard test, I2 statistic.Data synthesis When comparing misoprostol with medical vacuum aspiration (MVA), the rate of complete abortion was higher in the MVA group (OR = 0.16; 95%CI = 0.07–0.36). Hemorrhage or heavy bleeding was more common in the misoprostol group (OR = 3.00; 95%CI = 1.96–4.59), but pain after treatment was more common in patients treated with MVA (OR = 0.65; 95%CI = 0.52–0.80). No statistically significant differences were observed in the general acceptability of the treatments.Conclusion Misoprostol has been determined as a safe option with good acceptance by patients.
Keywords: Abortion; Miscarriage; Misoprostol; Curettage